Deteccion del virus del mosaico del dasheen en Araceas por la tecnica de radioinmunoensayo - Salazar, I.=700 1 Roy, A.; Gomez, L.; Arias, O.
Es, En)
Ilus., 8 ref.
Keywords: ARACEAE; XANTHOSOMA; VIROSIS; SINTOMAS; TECNICAS RADIOINMUNOLOGICAS; COSTA RICA; VIRUS DEL MOSAICO DEL DASHEEN; AGRONOMIA COSTARRICENSE